'Rules of Thumb' for Sovereign Debt Crises - Roubini, Nouriel (IMF Working Papers; Working Paper, 2005)
This paper contains an empirical investigation of the set of economic and political conditions that are associated with a likely occurrence of a sovereign debt crisis. We use a new statistical approach (Binary Recursive Tree) that allows us to derive a collection of "rules of thumb" that help identify the typical characteristics of defaulters. We find that not all crises are equal: they differ depending on whether the government faces insolvency, illiquidity, or various macroeconomic risks. We also characterize the set of fundamentals that can be associated with a relatively "risk free" zone. This classification is important for discussing appropriate policy options to prevent crises and improve response time and prediction.